STUDY OF FIRE RETARDANT AND FLAT WISE COMPRESSIVE PROPERTIES OF 3D WOVEN SANDWICH GLASS FIBRE â POLYESTER COMPOSITE FOR LIGHTWEIGHT TRAIN FLOOR APPLICATION - Ihsan Taufiq, Dodi
3D woven sandwich composites had high delamination resistance, but have lower core compressive properties than other sandwich material types. 3D sandwich composites would be applied to the light railroad floor panels in Indonesia to reduce the weight of train cars. In this application, in addition to the required low density and appropriate dimensions, it also required fire resistance and compressive properties that meet the railroad floor criteria. In this study, the fire resistance and compressive properties of 3D woven sandwich composites were examined. 3D woven sandwich composites were made by manual lamination method with the addition of aluminum hydroxide and the number of preform layers. Fire resistance properties were evaluated by combustion testing according to ORE B 102 standard. Compressive properties of the skin side composite core were evaluated by compressive testing. Composite woven glass fiber-polyester 3D sandwich compositions for Indonesian light rail floor panel applications have been successfully made with a composition: 3 layers of 3D woven preform, minimum 1 layer of 2D preform, and a minimum aluminum hydroxide weight ratio of 40%. This sandwich composite has a density of 0.448 g / cm3, thickness of 19.71 mm, category A fire resistance, compressive stiffness of 42.24 MPa, and compressive strength of 3.58 MPa. The addition of aluminum hydroxide increases the density of the sandwich composite. The addition of aluminum hydroxide increased the fire resistance of sandwich composites. The addition of aluminum hydroxide and the addition of a 3D glass fiber preform layer increased the stiffness and compressive strength of the skin side of the composite composite 3D glass fiber-woven sandwich.